Jeeves and the king of clubs : a novel in homage to P.G. Wodehouse - Schott, Ben, 1974- (Little, Brown and Company, 2018)
As a member of the Junior Ganymede Club--an association of butlers and valets that is in reality an arm of the British intelligence service--Jeeves must ferret out a Fascist spy, with the help of his hapless employer, Bertie Wooster.